PENGARUH MAKNA KERJA TERHADAP KOMITMEN AFEKTIF DENGAN VARIABEL PEMEDIASI KETERIKATAN KERJA PADA KARYAWAN BANK MANDIRI AREA BANDA ACEH - Shabir Abdul Majid; Mahdani Mahdani (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
Abstract: This study aims to discuss the meaning of work on affective commitment with the mediating variable is the work attachment to employees of Bank Mandiri in the Banda Aceh area. The sampling method in this study used simple random sampling with a total sample of 116 respondents. Data collection equipment used in this study is a questionnaire. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of all the variables involved. The results of the study indicate the variable meaning of work and significant work attachment to affective commitment. Furthermore, the work attachment variable mediates partially between the meaning of work on affective commitment.Keywords: Meaning of work, affective commitment, work engagement